Serum albumin nanoparticles: Ligand functionalization for enhanced targeted therapeutics in precision medicine - Sakshi Shahapurmath; Bhuvaneshwari R. Sharannavar; Rahul Koli (Medicine in Drug Discovery)
Serum albumin-based nanoparticles, derived from bovine (BSA) and human (HSA) sources, have emerged as versatile carriers in drug delivery systems due to their intrinsic biocompatibility, biodegradability, and amenability to surface modification. This review provides a comprehensive analysis of recent advancements in the functionalization of albumin nanoparticles with diverse ligands to enhance targeting specificity and therapeutic efficacy. Functional moieties such as folic acid, peptides, aptamers, antibodies and their fragments, polymers, chitosan, hyaluronic acid, biotin, transferrin, cholesterol, surfactants, and apolipoproteins have been extensively explored for their role in modulating cellular uptake, drug release kinetics, and site-specific accumulation. A systematic discussion of ligand selection, conjugation strategies, and encapsulated therapeutics is presented, along with a comprehensive evaluation of in vitro and in vivo studies assessing the pharmacokinetics, biodistribution, and therapeutic potential of ligand modified albumin nanoparticles. Particular empHSAis is placed on the applications of functionalized albumin nanoparticles in oncology, inflammatory and neurological disorders, and infectious diseases. Emerging trends highlight the development of multifunctional nanocarriers integrating imaging agents for theranostic applications and the application of cutting-edge functionalization techniques to facilitate personalized medicine. This review serves as a critical resource for researchers, fostering advancements in the rational design and optimization of albumin-based nanocarriers for precision drug delivery.